Sociality: constitutional and legal guarantees for fulfilling the tasks of the state, activating the individuals and preventing dependency - Avakyan, Suren A. (Journal of the Belarusian State University. Law, 2020)
While realizing the goals of his research, the author starts from the fact that sociality is a public unifying task based on the system of public relations of the state, civil society in general and especially associations of citizens in the implementation of their individual abilities and efforts not only in terms of self-support, but also in terms of assistance to others, society and the state. The article is based on the methods of author’s analysis, comparison and generalization. The importance of the research is determined by the fact that this aspect the problem is not yet sufficiently studied both in Russian Federation and in the Republic of Belarus. The author’s conclusions may be useful for the improvement of legislation.